2017
DOI: 10.1016/j.ijpharm.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Critical material attributes (CMAs) of strip films loaded with poorly water-soluble drug nanoparticles: III. Impact of drug nanoparticle loading

Abstract: Polymer strip films have emerged as a robust platform for poorly water-soluble drug delivery. However, the common conception is that films cannot exceed low drug loadings, mainly due to poor drug stability, slow release, and film brittleness. This study explores the ability to achieve high loadings of poorly water-soluble drug nanoparticles in strip films while retaining good mechanical properties and enhanced dissolution rate. Aqueous suspensions containing up to 30 wt% griseofulvin nanoparticles were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…prednisolone) [49], and micronization of the API to reduce its particle size [50]. Particle size reduction is an often used method to improve the solubility of poorly watersoluble APIs [51][52][53][54][55][56]. Krull et al showed that the dissolution of poorly water-soluble griseofulvin can be enhanced by using wetmilled drug particles.…”
Section: Local and Systemic Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…prednisolone) [49], and micronization of the API to reduce its particle size [50]. Particle size reduction is an often used method to improve the solubility of poorly watersoluble APIs [51][52][53][54][55][56]. Krull et al showed that the dissolution of poorly water-soluble griseofulvin can be enhanced by using wetmilled drug particles.…”
Section: Local and Systemic Drug Deliverymentioning
confidence: 99%
“…Krull et al showed that the dissolution of poorly water-soluble griseofulvin can be enhanced by using wetmilled drug particles. These (nano)particles were incorporated into a pullulan-based film [51] and hypromellose-based films [52,53].…”
Section: Local and Systemic Drug Deliverymentioning
confidence: 99%
“…The film is hydrated by saliva when placed on the tongue and disintegrates rapidly, releasing the active substance for local (oromucosal) or systemic (gastrointestinal) absorption, without the risk of choking [7]. This does not mean, however, that the drug itself dissolves quickly, and for poorly soluble drugs, it can be still a challenge to obtain fast dissolution and absorption [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that polymeric nanoparticles (NPs) can be used to improve the water solubility and stability of hydrophobic drugs (Levard et al, 2012;Krull et al, 2017). Therefore, CUR-loaded polymer NPs can prevent these molecules from being oxidized and improve their stability as well as their bioavailability.…”
Section: Introductionmentioning
confidence: 99%